Within-Leaf Nitrogen Allocation in Adaptation to Low Nitrogen Supply in Maize during Grain-Filling Stage - Mu, Xiaohuan; Chen, Qinwu; Chen, Fanjun; Yuan, Lixing; Mi, Guohua (Frontiers in Plant Science, 2016)
Nitrogen (N) plays a vital role in photosynthesis and crop productivity. Maize plants may be able to increase physiological N utilization efficiency (NUtE) under low-N stress by increasing photosynthetic rate (Pn) per unit leaf N, that is, photosynthetic N-use efficiency (PNUE). In this study, we analyzed the relationship between PNUE and N allocation in maize ear-leaves during the grain-filling stage under low N (no N application) and high N (180 kg N ha−1) in a 2-year field experiment. Under low N, grain yield decreased while NUtE increased. Low-N treatment reduced the specific N content of ear leaves by 38% without significant influencing Pn, thereby increasing PNUE by 54%. Under low-N stress, maize plants tended to invest relatively more N into bioenergetics to sustain electron transport. In contrast, N allocated to chlorophyll and light-harvesting proteins was reduced to control excess electron production. Soluble proteins were reduced to shrink the N storage reservoir. We conclude that optimization of N allocation within leaves is a key adaptive mechanism to maximize Pn and crop productivity when N is limited during the grain-filling stage in maize under low-N conditions.